The influence of raw material changes on gamut colour volume of a matt ceramic glaze - Varisli, Suleyman Onder; Anil, Umit Engin; Altindal, Fahriye; Ozturk, Bunyamin; Goren, Sumeyra Guven; Yilmaz, Senol (ELSEVIER SCI LTD, 2024)
This study aims to investigate the relationship between digital printing colour performance and the raw materials used in a matt glaze. Inkjet technology has enhanced the decorative properties of ceramic tiles in production. Improving the colour perception of the glaze is possible by optimizing the raw materials in the glaze, which results in less ink usage and thus lower costs. Investigation of the colour performance of glazes is possible by determining the L* a* b* values of the colours as well as the gamut colour volumes. Colour of the samples were evaluated by spectrophotometer and i1 profiler. Gamut volume was calculated by 3D CIE chromaticity diagrams of ICC profiles. It was observed that the colour saturation was higher in the samples where the pigment was homogeneously distributed in the glaze microstructure. SiO2 particles not embedded in the glass structure observed in the glaze microstructure disrupt the colour intensity. The low sphere temperature value of the composition made with wollastonite enabled the SiO2 particles to be embedded in the glaze. When wollastonite was used instead of dolomite as the source of calcium oxide in mat glaze, the colour gamut volume reached its highest value (11262), consequently increasing colour saturation. Conversely, the lowest colour gamut volume (6475) was obtained when dolomite was used instead of wollastonite.
Keywords: Glaze; Inkjet; Colour gamut; Floor tile; Materials Science